Prevalence of intestinal and blood parasites among wild rats in Kuala Lumpur, Malaysia - Shafiyyah, C.O.S.; Jamaiah, I.; Rohela, M.; Lau, Y.L.; Aminah, F.S. (2012)
A survey was undertaken to investigate the prevalence of intestinal and blood parasites among wild rats in urban area of Kuala Lumpur, Malaysia. A total of 137 stool and blood samples were collected from wild rats from Sentul and Chow Kit areas. Five species of rats were captured and supplied by Kuala Lumpur City Hall. The most common was Rattus rattus diardii (Malayan Black rat), 67, followed by Rattus norvegicus (Norway rat), 10, Rattus argentiventer (rice-field rat), 10, Rattus tiomanicus (Malaysian field rat), 9 and Rattus exulans (Polynesian rat), 4. Rattus rattus diardii is commonly known to live in human environment and they are normally identified as pests to human community. More male rats were captured (61) compared to female (39). Out of 137 samples, 81.8 samples were positive with intestinal parasites, with 86.2 from Sentul area and 78.5 from Chow Kit area. Six different parasites were detected. The most common intestinal helminth parasite detected was Nippostrongylus brasiliensis (80.3), followed by Hymenolepis nana (23.4), Capillaria hepatica (13.9) and Hymenolepis diminuta (2.9). Intestinal protozoan detected was Entamoeba histolytica/E. dispar (8.8). Trypanosoma lewisi (1.5) was the only blood parasite detected.